Accuracy of Implant Placement Utilizing Customized Patient Instrumentation in Total Knee Arthroplasty - William D. Bugbee; Hideki Mizu-uchi; Shantanu Patil; Darryl D'Lima (Advances in Orthopedics)
Customized patient instrumentation (CPI) combines preoperative planning with customized cutting jigs to position and align implants during total knee arthroplasty (TKA). We compared postoperative implant alignment of patients undergoing surgery with CPI to traditional TKA instrumentation for accuracy of implant placement. Twenty-five consecutive TKAs using CPI were analyzed. Preoperative CT scans of the lower extremities were segmented using a computer program. Limb alignment and mechanical axis were computed. Virtual implantation of computer-aided design models was done. Postoperative coronal and sagittal view radiographs were obtained. Using 3D image-matching software, relative positions of femoral and tibial implants were determined. Twenty-five TKAs implanted using traditional instrumentation were also analyzed. For CPI, difference in alignment from the preoperative plan was calculated. In the CPI group, the mean absolute difference between the planned and actual femoral placements was 0.67° in the coronal plane and 1.2° in the sagittal plane. For tibial alignment, the mean absolute difference was 0.9° in the coronal plane and 1.3° in the sagittal plane. For traditional instrumentation, difference from ideal placement for the femur was 1.5° in the coronal plane and 2.3° in the sagittal plane. For the tibia, the difference was 1.8° in the coronal plane. CPI achieved accurate implant positioning and was superior to traditional TKA instrumentation.